Solar electricity handbook a simple practical guide to solar energy : how to design and install photovoltaic solar electric systems - Boxwell, Michael (Greenstream Publishing, 2023)
A simple, practical guide to solar energy, designing and installing solar photovoltaic systems. Solar electricity is a wonderful concept. Take free power from the sun and use it to power electrical equipment. No ongoing electricity bills, no reliance on an electricity socket. 'Free' electricity that does not harm the planet. Generating electricity from sunlight alone is a powerful resource, with applications and benefits throughout the world. But how does it work? What is it suitable for? How much does it cost? How do I install it? This best-selling Internet-linked book answers all these questions and shows you how to use the power of the sun to generate electricity yourself. The website that accompanies this book includes online solar calculators and tools to simplify your solar installation, ensuring that building your system is as straightforward and successful as possible.